Influence of effective social and adaptive behaviour on personality adjustment of gifted underachievers and students with learning disabilities in Egbeda Local Government, Ibadan (2015)
This study investigated the influence of effective social and adaptive behaviour on personality adjustment among gifted underachievers and students with learning disabilities in Egbeda Local Government, Oyo State, Nigeria. The sample consisted of 205 SS1 and SS2 students (males=75, females=130), who were randomly selected in Egbeda Local Government. Instruments (self developed questionnaires) were used to measure the influence of social and adaptive behaviour on personality adjustment of these students. Data collected were analysed using Analysis of co-variance (ANOVA), Pearson Product Moment Correlation and Multiple Regression Analysis. Results of the findings indicated that, effective social and adaptive behaviour can influence openness to expression, conscientiousness, extraversion, agreeableness and neuroticism (personality adjustment) of gifted underachievers and students with learning disabilities. Also, gender had a significant relationship with personality adjustment.